Metode Lot Sizing untuk Menentukan Biaya Persediaan Beras pada Perum Bulog Kantor Cabang Semarang - Fayaqun, Reza; Sulistiyaningsih, Febriani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Food security is an important matter that is of concern to the government, through Bulog the Government controls rice supplies in the country, especially in the city of Semarang where there is a stock out, to overcome this problem a safety stock of 681.93 kg per month is needed as well as the application of three lotting techniques namely lot for lot, EOQ and LUC to determine which lotting technique produces the minimum total inventory cost. Of the three lotting techniques, the lot for lot technique is considered more profitable with a total inventory cost of Rp. 100,620,861 compared to using the EOQ lotting technique with a total inventory cost of Rp. 111,910,165 with a difference of Rp. 11,289,304 greater than the lot for lot lotting technique. The largest total inventory cost by applying LUC lotting is Rp. 128,058,510, with a difference in total inventory costs of Rp. 25,437,684 or 25.3% greater than lot-for-lot lotting, this is because in the simple EOQ model it is assumed that orders arrive all at once and will increase inventory, in reality, orders arrive according to the transport capacity, which is 4 tons. So it can be concluded that if these three lotting techniques are applied, the lot-for-lot technique has the lowest inventory costs.